Post-zygotic reproductive barriers confirm absence of continuous interspecific gene flow between Mepraia spp. (Hemiptera, Triatominae) - Jader de Oliveira; Kaio Cesar Chaboli Alevi; Amanda Ravazi; Jociel Klleyton S. Santana; Daniel Frias Lasserre; João Aristeu da Rosa; Cleber Galvão; Mauro Toledo Marrelli (Scientific Reports)
Abstract Mepraia is a genre composed of three species endemic to Chile. Climate projections demonstrate that these triatomines could modify their potential geographical range and does not rule out that hybridization events could be occurring. Furthermore, recent phylogenomic studies suggested possible ancestral events of hybridization and gene flow and, based on the most recent speciation model that divides Mepraia in two geographically distinct groups (the North, composed of M. garjadoi and M. parapatrica, and the South, composed of M. spinolai), was also suggested an alternative model that may be compatible with ancient hybridization events or continued gene flow. Thus, we conducted a comprehensive study of the capacity to produce hybrids and to reproductive barriers present between Mepraia spp., with the aim of evaluating the possibility of hybridization and interspecific gene flow be occurring in natural conditions and confirming the specific status of the three Mepraia species. Even though hybrids have been obtained in all directions, the combination of different evolutionary events demonstrated here, such as low hatching rate and high mortality rate of hybrids, as well as the presence of post-zygotic reproductive barriers and possible action of Haldane’s rule indicate that there is no continuous interspecific gene flow between Mepraia spp. and confirms the specific status of species based on the biological species concept.